La crítica al desarrollo entre lo tangible y lo intagible (2007)
ABSTRACT: This article presents the trends in the critique of development from its implementation as a social, economic, political and cultural paradigm, starting in the fourth decade of the twentieth century. These are approached in two ways: the first one corresponds to a search for completing development; it focuses on its difficulties in the prioritization of economic growth, poverty eradication, the impacts on the environmental equilibrium, the aims or the places where it materializes and the importance of the territory where it is applied. The second one focuses on the de-construction of the discourse and practice as a system of representation and action by which subjects and societies in the world perceive themselves, as developed and underdeveloped. This approach shows how science, technology, poverty, can be replaced by other ways of life.